A learning agenda for the advocacy evaluation field's future. Issue 171 (24th September 2021) - Coffman, Julia; Stachowiak, Sarah; Raynor, Jared
Abstract: This volume set out to document, illustrate, and critique the progress and innovation that has occurred during the advocacy evaluation field's first phase of development. This final chapter identifies how the context in which advocacy evaluation plays out is shifting. It describes how these shifts impact how advocates, advocacy funders, and advocacy evaluators think about what works, and what has value. Given this context, and lifting up the ideas of other chapter authors, the chapter concludes with a learning agenda for the field's next phase of development—four questions to help guide future field innovation and collective learning.